The Enduring Conflict in the Middle East: Irrational Causes and Viable Solutions that might begin with the Educational Means - Issa, Mohammad Saleh Bani (International Journal of Membrane Science and Technology, 2023)
This Paper aims at tracing and analyzing the irrational reasons that stood behind the lasting conflict in the Middle East with a refutation of its continuation according to the theory of recognition, as well as the viable solutions that might reduce the tension in the region and end the conflict for a long run. It discussed the reasons that caused the conflict in the region to continue for more than hundred years for the benefit of the colonial states. The paper reached a point that the colonial states were behind the establishment of Israel in the region to be used as a functional state for the perpetuation of colonialism in the region, despite the existence of a Jewish homeland that had been previously announced in Birobidzhan, before the declaration of Israel in Palestine that is why seen today a rebellious state against the legitimacy and international law. The study concluded that it has become necessary to explain more precisely to the youth the cause of the suffering experienced by the peoples of the region of their various races and religions through educational curriculum at all levels of school and university. The study also concluded some proposals that may contribute to ending the unjust conflict gradually in the future.